TINJAUAN HUKUM MARKETPLACE SHOPEE TERHADAP PERATURAN PASAL 31 POJK NOMOR 13/POJK.02/2018 DI INDONESIA - Sonia Ghanyyu Rebia (Jurnal Education and Development, 2023)
Buying and selling transactions of goods or products in this era of globalization are in great demand by consumers with technological advances that provide convenience for consumers in various fields, one of which is in the field of trade or buying and selling in consumers. will never be separated from buying and selling where trading continues. increased very significantly which changed the conventional economic system to digital. Responsibility in buying and selling online as a form to reduce losses received. Shopee's legal relationship with the seller is cooperation and power of attorney to shopee in a cooperation agreement. Where shopee is the provider of the application platform/site and the seller is the provider of goods. In the legal relationship between the parties in the digital marketplace system transaction since the agreement, both the agreement between the seller as a Shopee partner and the Shopee marketplace or the Shopee marketplace with the buyer as a consumer, cooperate with each other and/or bind themselves in accordance with the terms and conditions that apply in the contents of the market agreement. and has fulfilled the subjective and subjective requirements of Article 1320 of the Civil Code.